2013
DOI: 10.1371/journal.pone.0071882
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Murine Passive Immune Thrombocytopenia by IVIg and a Therapeutic Monoclonal CD44 Antibody Does Not Require the Myd88 Signaling Pathway

Abstract: Immune thrombocytopenia (ITP) is an autoimmune bleeding disorder characterized by a low platelet count and the production of anti-platelet antibodies. The majority of ITP patients have antibodies to platelet integrin αIIbβ3 (GPIIbIIIa) which can direct platelet phagocytosis by macrophages. One effective treatment for patients with ITP is intravenous immunoglobulin (IVIg) which rapidly reverses thrombocytopenia. The exact mechanism of IVIg action in human patients is unclear, although in mouse models of passive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The efficacy of anti-CD44 antibodies has been evaluated in murine models of autoimmune and inflammatory diseases including thrombocytopenia and arthritis. Immune thrombocytopenia is an autoimmune bleeding disorder characterized by a low platelet count and the production of anti-platelet antibodies ( 119 , 120 ). While the standard treatment for immune thrombocytopenia is passive infusion of immunoglobulins, several anti-CD44 antibodies have been shown to ameliorate immune thrombocytopenia.…”
Section: Targeting Ha Receptorsmentioning
confidence: 99%
“…The efficacy of anti-CD44 antibodies has been evaluated in murine models of autoimmune and inflammatory diseases including thrombocytopenia and arthritis. Immune thrombocytopenia is an autoimmune bleeding disorder characterized by a low platelet count and the production of anti-platelet antibodies ( 119 , 120 ). While the standard treatment for immune thrombocytopenia is passive infusion of immunoglobulins, several anti-CD44 antibodies have been shown to ameliorate immune thrombocytopenia.…”
Section: Targeting Ha Receptorsmentioning
confidence: 99%
“…Some studies have demonstrated the effectiveness of IVIG in increasing the PLT count and the potential mechanism by using the passive model. 25,26 This ITP model can reflect the progression stage of ITP and has been extensively utilized to rapidly evaluate the efficacy of various therapeutic options. 27,28 In our study, we induced an improved passive ITP mouse model by dose-escalation injection of the anti-CD41 antibody MWReg30 daily and found that the PLT counts were significantly increased on the 2nd day and remained at relatively high levels to alleviate bleeding symptoms after MSC administration.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the passive model can prevent the rebound of PLTs and monitor the efficacy of therapeutics more sensitively. Some studies have demonstrated the effectiveness of IVIG in increasing the PLT count and the potential mechanism by using the passive model . This ITP model can reflect the progression stage of ITP and has been extensively utilized to rapidly evaluate the efficacy of various therapeutic options .…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies to CD44 as well as intravenous immune globulin (IVIG) can both be used to treat murine passive immune thrombocytopenia (ITP), an acute model in which a PLT antibody is passively administered to induce thrombocytopenia in an FcγRIIIa‐dependent (Teeling et al . and Crow & Lazarus, unpublished, 2003), complement‐independent manner.…”
Section: Comparison Of Anti‐cd44 and Ivig Responses In Published Animmentioning
confidence: 99%